2019
DOI: 10.34019/2596-3325.2019.v20.26103
|View full text |Cite
|
Sign up to set email alerts
|

Amphisbaenia: Adaptações para o Modo de Vida Fossorial

Abstract: Amphisbaenia são répteis fossoriais, que vivem em sistemas de túneis construídos por eles mesmos. Atualmente, são descritas 195 espécies recentes. O objetivo deste estudo foi reunir informações bibliográficas sobre aspectos de sua morfologia, fisiologia e comportamento relacionando-as ao hábito fossorial. O principal instrumento de escavação dos anfisbênios é a cabeça, cuja morfologia está relacionada com a maneira como a escavação é realizada. Assim, nas espécies com a cabeça arredondada o mecanismo de escava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…If we assume that inter‐ and intraspecific competition is negligible for tail loss in Amphisbaena vermicularis , urotomy frequency can be interpreted as an indicative of predation intensity or efficiency. Despite criticism regarding the use of urotomy frequency as an index of predation (Jaksić & Busack, 1984; Jaksić & Greene, 1984), this seems a valid assumption for A. vermicularis since there is no evidence suggesting that intraspecific competition plays any role in tail breakage of worm lizards; the lost tail keeps moving after being autotomized, which could distract predators (Navega‐Gonçalves & Benites, 2019; Papenfuss, 1982); and the tail can only be shed once (Gans, 1978), making it a unique antipredatory behavior (Brito et al., 2001). Regardless of these issues, we herein hope to reduce existing knowledge gaps between worm lizards and other squamates regarding patterns and processes of urotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we assume that inter‐ and intraspecific competition is negligible for tail loss in Amphisbaena vermicularis , urotomy frequency can be interpreted as an indicative of predation intensity or efficiency. Despite criticism regarding the use of urotomy frequency as an index of predation (Jaksić & Busack, 1984; Jaksić & Greene, 1984), this seems a valid assumption for A. vermicularis since there is no evidence suggesting that intraspecific competition plays any role in tail breakage of worm lizards; the lost tail keeps moving after being autotomized, which could distract predators (Navega‐Gonçalves & Benites, 2019; Papenfuss, 1982); and the tail can only be shed once (Gans, 1978), making it a unique antipredatory behavior (Brito et al., 2001). Regardless of these issues, we herein hope to reduce existing knowledge gaps between worm lizards and other squamates regarding patterns and processes of urotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens may eventually forage above the ground (Aragão et al, 2019), and there are predation records by snakes (França et al, 2008; Lisboa & Freire, 2010; Oliveira et al, 2014), a frog (Vaz‐Silva, Silva, & Silva Junior, 2003), and birds (Nolasco et al, 2020). Aggressive intraspecific interactions or even defensive behaviors are not reported for A. vermicularis , except for observations of captive specimens “jumping” to escape when placed over hard soil – unable to dig as an escaping mechanism (Navega‐Gonçalves & Benites, 2019). However, as reported for other South American species (Brito et al., 2001), tail autotomy may indeed represent an antipredatory behavior for A. vermicularis .…”
Section: Introductionmentioning
confidence: 99%
“…The amphisbaenian diet consists of a variety of invertebrates and small vertebrates (Gans, 1969;Navega-Gonçalves and Benites, 2019), and most amphisbaenian species appear to be dietary generalists (Bernardo-Silva et al, 2006;Gomes et al, 2009;Balestrin and Cappellari, 2011;Martín et al, 2013), although some species have a more selective diet, which indicates that they are specialists (Webb et al, 2000;Vega, 2001;Al-Sadoon et al, 2016). These studies showed that the amphisbaenian diet consists primarily of small arthropods found in the subsoil, including ants, termites, beetles, and spiders.…”
Section: Introductionmentioning
confidence: 99%
“…The paucity of information on the natural history and biogeography of amphisbaenians is in most part due to their fossorial habits, making them difficult to find. As result, this is one of the least known groups of Squamata (Vitt and Caldwell 2014, Costa and Garcia 2019, Navega-Gonçalves and Benites 2019. Amphisbaena mertensii Strauch, 1881 is a worm lizard with a broad geographic range, occurring in southeastern and west-central Brazil, eastern Paraguay, and northeastern Argentina (Gans 1966, Corrêa andMeneses 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Amphisbaena mertensii Strauch, 1881 is a worm lizard with a broad geographic range, occurring in southeastern and west-central Brazil, eastern Paraguay, and northeastern Argentina (Gans 1966, Corrêa andMeneses 2020). Among South American amphisbaenians, A. mertensii is relatively well-studied, including data on activity (Moraes and Recchia 2011), defensive behavior (Brito et al 2001, Andrade et al 2006, Navega-Gonçalves and Benites 2019), diet and feeding behavior (Cruz-Neto and Abe 1993, Pramuk and Alamillo 2003, Moraes and Recchia 2011, Navega-Gonçalves and Benites 2019, predation (Sazima and Abe 1991, Duarte 2006, Barbo and Sawaya 2008, Barbo et al 2011, Rodríguez et al 2018), reproduction (Pramuk and Alamillo 2003, Andrade et al 2006, Aguirre et al 2017, thermal ecology (Abe 1984), distribution and habitat (Pramuk and Alamillo 2003, Ribeiro et al 2007, Moraes and Recchia 2011, Silveira et al 2012, Corrêa and Meneses 2020, cytogenetics (Hernando 2005) and anatomy Souza 2001, Gans andMontero 2008). This species can be found in environments of native vegetation (Zaracho et al 2014), pasturelands (Pramuk and Alamillo 2003), and even urban areas (Barbo and Sawaya 2008, Moraes and Recchia 2011, Silveira et al 2012.…”
Section: Introductionmentioning
confidence: 99%